2007
DOI: 10.1038/sj.clpt.6100157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ABCB1 Polymorphism on the Pharmacokinetics of Saquinavir Alone and in Combination with Ritonavir

Abstract: This genotype panel study investigated the effect of ABCB1 polymorphism in exon 26 (C3435T), exon 21 (G2677T/A), and exon 12 (C1236T) on saquinavir pharmacokinetics and on the expression and activity of P-glycoprotein (P-gp) in peripheral blood monocytic cells (PBMCs). One hundred and fifty healthy volunteers were genotyped to identify 15 TT3435 and 15 CC3435 individuals. In these individuals, saquinavir pharmacokinetics were assessed after administration of a single oral dose of saquinavir 1,000 mg and saquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In HIV-infected patients, 2677G>T/A and 3435C>T genotypes, separately or as haplotypes, were not associated with clinical response to unboosted indinavir-containing regimens (Verstuyft et al, 2005). In healthy Canadian volunteers, 1236C>T, G2677G>T/A, and 3435C>T genotypes, separately or as haplotypes, were not associated with saquinavir pharmacokinetics, unboosted or boosted with ritonavir (la Porte et al, 2007). In contrast with these haplotype-based results, the 3435CT genotype was associated with virological efficacy in antiretroviral-naïve HIV-infected patients on an unboosted PI-containing regimen, but not in patients on a boosted PI-containing regimen (de la Tribonniere et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-infected patients, 2677G>T/A and 3435C>T genotypes, separately or as haplotypes, were not associated with clinical response to unboosted indinavir-containing regimens (Verstuyft et al, 2005). In healthy Canadian volunteers, 1236C>T, G2677G>T/A, and 3435C>T genotypes, separately or as haplotypes, were not associated with saquinavir pharmacokinetics, unboosted or boosted with ritonavir (la Porte et al, 2007). In contrast with these haplotype-based results, the 3435CT genotype was associated with virological efficacy in antiretroviral-naïve HIV-infected patients on an unboosted PI-containing regimen, but not in patients on a boosted PI-containing regimen (de la Tribonniere et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…172 Thus, the marginal decrease in the exposure of these drugs might be a mixed effect involving intestinal OATPs and CYP3A. Additionally, inhibition of intestinal P-gp may be also involved in the interaction between quercetin and saquinavir, as both in vitro 110,118,156,163,[173][174][175][176][177][178][179][180][181][182][183][184] and clinical investigations [185][186][187][188] suggest that saquinavir is a substrate of P-gp and quercetin is an inhibitor of P-gp. 189,190 The mechanisms of interactions with the remaining 4 drugs remain undetermined.…”
Section: Additional Drugsmentioning
confidence: 99%
“…Surprisingly, we found that HIV-1-infected children heterozygotes MDR1 1236CT had a significantly lower LPV plasma concentration (C post-dose ) compared to homozygotes MDR1 1236TT. However, la Porte et al (2007) did not found significant correlation between this polymorphism and saquinavir C max in adult healthy volunteers. In addition, we did not observed a significant association between MDR1 C1236T genotypes and LPV trough concentration in accordance with a previous study of Estrela et al (2009) performed in HIV-infected Brazilian adult males.…”
Section: Discussionmentioning
confidence: 71%